Deciphering the effects of nelfinavir and lopinavir on epimastigote forms of Trypanosoma cruzi. Issue 5 (October 2017) - Sangenito, Leandro Stefano; de Guedes, Arthur A.; Gonçalves, Diego S.; Seabra, Sergio H.; d'Avila-Levy, Claudia M.; Santos, André L.S.; Branquinha, Marta H.
Graphical abstract: Highlights: Some aspects of T. cruzi epimastigote's physiology and biochemistry are demonstrated. Nelfinavir and lopinavir reduce the aspartyl peptidase and proteasome activities. Nelfinavir and lopinavir affect epimastigote's viability inducing cellular damages. Both compounds impaired the mitochondrial functions of epimastigotes. The lipid storage in T. cruzi epimastigotes are affected by the treatment.